Transformasi Padi Indica Kultivar Batutegi dan Kasalath dengan Gen Regulator HD-Zip untuk Perakitan Varietas Toleran Kekeringan - Enung Sri Mulyaningsih; Hajrial Aswidinnoor; Didy Sopandie; Pieter B.F. Ouwerkerk; Inez Hortense Slamet Loedin (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2010)
water deficiency. Genetic engineering at the level of transcription factors (TF) is particulary a promising strategy in developing drought tolerant rice cultivar. HD-Zip genes are TF that function in plant adaptation to some environmental stresses including water deficit. The recombinant plasmid pC1301H Oshox6 which contained HD-Zip Oshox6 gene was placed under a drought inducible promoter called LEA promoter, gusA and hpt genes were driven with CaMV promoter. The aim of research was to obtain indica rice transgenic plants of Batutegi and Kasalath cultivars using pC1301H Oshox6 plasmid. Recombinant plasmid was transformed into immature rice embryos using Agrobacterium tumefaciens. Kasalath cultivar showed a better capacity to form embryogenic calli compared to Batutegi. Transformation efficiency of Batutegi is lower (1.5 - 0.3%) than Kasalath (2.2-28.3%). Regeneration efficiency is 25-83.3% and 7.7-100% for Batutegi and Kasalath, respectively. Number of putative transformant plantlets of Batutegi and Kasalath are 63 and 48 plantlets, respectively. Southern blot analysis (using hpt probe) on 12 independent lines of each Batutegi and Kasalath cultivars showed different gene copy number, ranging from one to four copies of gene. Keywords: agrobacterium tumefaciens, LEA promoter, HD-Zip Oshox6, rice